Dynamic changes in host–virus interactions associated with colony founding and social environment in fire ant queens (Solenopsis invicta). Issue 1 (29th December 2015) - Manfredini, Fabio; Shoemaker, DeWayne; Grozinger, Christina M.
Abstract: The dynamics of host– parasite interactions can change dramatically over the course of a chronic infection as the internal (physiological) and external (environmental) conditions of the host change. When queens of social insects found a colony, they experience changes in both their physiological state (they develop their ovaries and begin laying eggs) and the social environment (they suddenly stop interacting with the other members of the mother colony), making this an excellent model system for examining how these factors interact with chronic infections. We investigated the dynamics of host– viral interactions in queens of Solenopsis invicta (fire ant) as they transition from mating to colony founding/brood rearing to the emergence of the first workers. We examined these dynamics in naturally infected queens in two different social environments, where queens either founded colonies as individuals or as pairs. We hypothesized that stress associated with colony founding plays an important role in the dynamics of host– parasite interactions. We also hypothesized that different viruses have different modalities of interaction with the host that can be quantified by physiological measures and genomic analysis of gene expression in the host. We found that the two most prevalent viruses, SINV‐1 and SINV‐2, are associated with different fitness costs that are mirrored by different patterns of gene expression in the host. In fact SINV‐2, the virus that imposes the significant reduction of a queen's reproductive output is also associated with larger changes of global gene expression in the host. These results show the complexity of interactions between S. invicta and two viral parasites. Our findings also show that chronic infections by viral parasites in insects are dynamic processes that may pose different challenges in the host, laying the groundwork for interesting ecological and evolutionary considerations. Abstract : Founding a new colony is a challenging time for newly mated queens of the fire ant Solenopsis invicta . Viral infections are one of the major challenges as they can cause mortality and reduce a queen's reproductive output. Here, we describe natural associations of fire ant queens with two viruses by following the patterns of infection and by characterizing the queen's response at the physiological and molecular levels.